Antibacterial activities of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) against planktonic and biofilm growing Streptococcus mutans. (June 2017) - Sun, Mengjun; Dong, Jiachen; Xia, Yiru; Shu, Rong
Abstract: The aim of this study was to evaluate the potential antibacterial activities of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) against planktonic and biofilm modes of Streptococcus mutans ( S. mutans ). The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined. The effects on planktonic growth and biofilm metabolic activity were evaluated by growth curve determination and MTT assay, respectively. Then, colony forming unit (CFU) counting, scanning electron microscopy (SEM) and real-time PCR were performed to further investigate the actions of DHA and EPA on exponential phase- S. mutans . Confocal laser scanning microscopy (CLSM) was used to detect the influences on mature biofilms. The MICs of DHA and EPA against S. mutans were 100 μM and 50 μM, respectively; the MBC of both compounds was 100 μM. In the presence of 12.5 μM–100 μM DHA or EPA, the planktonic growth and biofilm metabolic activity were reduced in varying degrees. For exponential-phase S. mutans, the viable counts, the bacterial membranes and the biofilm-associated gene expression were damaged by 100 μM DHA or EPA treatment. For 1-day-old biofilms, the thickness was decreased and the proportion of membrane-damaged bacteria was increased in the presence of 100 μM DHA or EPA. These results indicated that, DHA and EPA possessed antibacterial activities against planktonic and biofilm growing S. mutans . Highlights: DHA and EPA showed antibacterial activities on planktonic and biofilm growing S. mutans. DHA and EPA damaged the bacterial plasma membrane of S. mutans. DHA and EPA decreased the biofilm-associated gene expression of S. mutans.